Dopamine/adenosine interactions involved in effort-related aspects of food motivation - Salamone, John D. (2009)
Nucleus accumbens dopamine (DA) is involved in effort-related aspects of food motivation. Accumbens DA depletions reduce the tendency of rats to work for food, and alter effort-related choice, but leave other aspects of food motivation and appetite intact. DA and adenosine receptors interact to regulate effort-related processes. Adenosine A(2A) antagonists can reverse the effects of DA D(2) antagonists on effort-related choice, and intra-accumbens injections of a adenosine A(2A) agonist produce effects that are similar to those produced by accumbens DA depletion or antagonism. These studies have implications for understanding the neurochemical interactions that underlie activational aspects of motivation.